A Reconsideration of Nathaniel Hawthorne’s The Scarlet Letter - Uçum, Uğur (Journal of History Culture and Art Research, 2015)
A Reconsideration of Nathaniel Hawthorne’s The Scarlet Letter Abstract This paper aims at offering an in-depth analysis of both the 1926 and the 1995 movie adaptations of Nathaniel Hawthorne’s 1850 novel The Scarlet Letter. Caught in a story of love and shame, of sin and salvation, Hester Prynne oscillates between Roger Chillingworth and Arthur Dimmesdale, two men too coward to bear the consequences of their actions. Why is Hester’s story still fascinating today? Will contemporary readers be willing to read the 1850 novel? Which are the main differences between the 2 movie adaptations? These are only a few of the questions this paper focuses upon.